RELASI INTERPERSONAL DALAM PSIKOLOGI KOMUNIKASI - Rustini Wulandari; Amelia Rahmi (Islamic Communication Journal, 2018)
Survival of human life is proof that human being able to solve and fulfill requirements of life which is individual and also social. Human life is a building interpersonal relationship with each other, called interpersonal relationship. The more an active person building relationships with others it will build an extensive interpersonal network and produce quality self-competence. This is what can bring success in many ways. Generally humans can adjust to the situation faced by learning the previous experience. Overtime the relationshipÂ  develops an individual character. The psychological aspect of both parties involved in the relationship are more decesive compared with sociological and cultural aspects. The existence of psychological aspect that determine the process of interpersonal communication has led to a specific study in interpersonal relationships into studies in this article, although the study has not been based on in-depth research.Keywords: communication, psychology, interpersonal relationship-----------------------------------------------------------------------------------Kelangsungan hidup manusia di muka bumi hingga kini merupakan bukti bahwa manusia mampu menyelesaikan dan memenuhi kebutuhan yang bersifat individu dan sekaligus sosial.Kehidupan ini merupakan bangunan relasi antarpersonal satu dengan yang lainnya, disebut relasi interpersonal. Semakin seseorang aktif membangun relasi dengan sesama maka akan terbangun jaringan interpersonal yang luas dan menghasilkan kompetensi diri yang berkualitas. Hal inilah yang dapat membawa kesuksesan dalam banyak hal.Umumnya, manusia dapat menyesuaikan dengan situasi yang dihadapi dengan cara mempelajari pengalaman sebelumnya. Seiring dengan waktu hubungan berkembanglah sebuah karakter individu. Aspek-aspek psikologis yang dimiliki kedua belah pihak yang terlibat dalam relasi lebih menentukan dibanding dengan aspek sosiologis dan kultural.Adanya aspek psikologis yang menentukan proses komunikasi interpersonal telah memunculkan kajian spesifik dalam relasi interpersonal menjadi kajian dalam artikel ini, meskipun kajiannya belum berbasis riset secara mendalamÂ Kata kunci: komunikasi, psikologi, relasi interpersonal.